Unraveling the Merdeka Curriculum: Exploring Differentiated Instruction’s Impact on Student Learning - Samsudi, Samsudi; Supraptono, Eko; Utanto, Yuli; Rohman, Shohihatur; Djafar, Tasliati (Jurnal Ilmiah Peuradeun, 2024)
Differentiated instruction, as the application of the ‘teaching at the right level’ principle, which involves tailoring teaching to student’s needs and the diversity of their interests and readiness, needs to be developed in Merdeka Curriculum implementation. This research aimed to measure the influence of learning components, including variables such as planning, implementation, and learning assessment, as well as learning elements, including variables such as content, processes, learning outcomes, and the learning environment, on the potential for differentiated instruction in elementary and secondary education. This research employed a quantitative method, using path analysis to measure the significance of the influence of independent variables (learning components and learning elements) on the potential for differentiated instruction. The results indicated that three variables significantly influence the Potential for Differentiated Instruction (Y), namely: Learning Components/ Learning Assessment (X3) with a t-value of 12.817 > ttable1,985; Learning Elements/ Learning Processes (X5) with a t-value of 10.223 > t ttable 1,985; and Learning Outcomes/ Achievements (X6) t-value 9.817 > ttable 1,985. Thus, the potential for differentiated instruction in Merdeka Curriculum implementation in elementary and secondary education can be maximized if teachers can plan and implement learning assessments accurately, manage differentiated instruction processes, and apply differentiated instruction outcomes.